Variação da demanda química de oxigênio (DQO) em mananciais do município de Araraquara-SP. Parte I - 1989 - Rocha, Júlio Cesar; Cardoso, Arnaldo Alves; Barbiéri, Roberto Santos; Magnani, Romeu (Eclética Química, 1990)
.